Experiencing pain: electromagnetic waves, consciousness, and the mind - Ambron, Richard (Frontiers in Human Neuroscience, 2025)
Studies of nociception resulted in a theory in which the quality of pain – the suffering - arises when action potentials (APs) from the thalamus that encode information about an injury induce a long-term potentiation (LTP) at synapses on pyramidal neurons in a pain center (PC) within the anterior cingulate cortex (ACC). The LTP sensitizes transmission across the synapses via the activation of adenylate cyclase-1 (AC-1) and protein kinase A (PKA). It also generates Electromagnetic (EM) waves that now contain the information about the pain. The pain is experienced when the waves reach consciousness. Blocking the AC-1, PKA, or the waves attenuates the pain. The theory was founded on the response to a simple injury. I now discuss the role of other cortical centers involved in pain. Attention to pain is governed by circuits in the anterior insula cortex (IC); fear, which enhances the intensity of pain, involves circuits in the basal nucleus of the amygdala; and reward, which can attenuate pain, is regulated by activity in the nucleus accumbens (NucA). Evidence shows that injury-evoked APs induce LTP and the generation of EM waves in the IC, amygdala, and the NucA. Interactions between the waves from the PC with those from the amygdala or NucA can enhance or reduce pain, respectively. These findings reinforce the earlier theory that the information in the EM waves results in sensory experiences in consciousness. I now propose that the summation of the sensory experiences becomes knowledge in the mind, which is an entity distinct from the brain.